Toward Improved Diagnosis Accuracy and Treatment of Children, Adolescents, and Young Adults With Ependymoma: The International SIOP Ependymoma II Protocol - Leblond, Pierre; Massimino, Maura; English, Martin; Ritzmann, Timothy A.; Gandola, Lorenza; Calaminus, Gabriele; Thomas, Sophie; Pérol, David; Gautier, Julien; Grundy, Richard G.; Frappaz, Didier (Frontiers in Neurology, 2022)
Background. The clinical management of ependymoma in childhood and adolescence is complex and the clinico-bio-pathological correlates of outcome remain poorly understood. This international SIOP Ependymoma II (SIOP EPII) trial aims to improve the outcome of patients with ependymoma. Methods. SIOP EPII includes any patient <22y at diagnosis with ependymoma, stratified by age, tumour location and outcome of the initial surgery. Centralised pathology and imaging is required for diagnosis confirmation. SIOP EPII included three randomised studies according to age, post-operative residue and suitability to receive radiotherapy. Patients ineligible for interventional strata are followed-up in an observational study. The staging phase aims to determine if central neurosurgical and radiological post-operative MRI reviews increase resection rate. Patients ≥12 months with i) no residual disease are randomly assigned in a phase III trial to evaluate the efficacy of post-radiation 16-week chemotherapy (VEC+CDDP) on PFS (Stratum I); ii) centrally confirmed measurable inoperable residual disease are allocated to randomised frontline chemotherapy phase II study (VEC vs VEC+high-dose methotrexate) and considered for a second look surgery (stratum II). If second look surgery is not feasible or tumour residuum remains, patients receive an 8Gy-boost radiotherapy after conformal radiotherapy (Phase I). iii) Patients <12 months (18 months in UK) or not eligible to receive radiotherapy are randomised in a phase II study to receive chemotherapy (alternated myelosuppressive and non myelosuppressive chemotherapy), with or without valproate (Stratum III). In order to overcome the limitations encountered in the preliminary conclusions of the ACNS-0831 study, a SIOP EPII dedicated on-study amendment has been planned to definitively conclude on the relevance of maintenance chemotherapy in stratum I. Secondary outcomes include overall survival, quality of life, neuropsychological and neuroendocrine outcomes, safety, and identification of key prognostic biomarkers (BIOMECA).